Petrography and geochemistry of Pila Spi Formation (Middle- Late Eocene) in Selected Sections / Northern Iraq - A. Hussein, Lafta S. Kadhim, Sfoog (Iraqi Journal of Science, 2022)
The Pila Spi Formation (middle – late Eocene) was studied in terms of field character, Petrography and geochemistry from two outcrops (Bakhar and Bani bawy) sections, Northern Iraq. The field studies showing massive, lithified limestone to marly limestone high effected by dolomitization. The petrography studies shows that most of the skeletal grains was destroyed due to digenetic processes specifically the dolomitization, and the vast majority of carbonate rocks are mudstone and few beds of wackestone. The geochemical study reveals low CaO% and high MgO% content due to the intense effect of dolomitization, and the carbonate rocks was classified as impure limestone generally of slightly calcareous dolomite. Ca/Mg and Sr/Ca ratios have been used to evaluate the depositional environment and indicate near shore and shallow depth environment and the basin become shallower upward in both sections.